Prototyped Temporary Abutments as an Alternative to Polyether Ether Ketone Temporary Abutments - Valencia-Llanos, Carlos-Humberto; Muñoz-Vélez, Mario-Fernando; Rodríguez-Paz, Martha-Lucia; Mosquera-Victoria, Isabella; Viveros-Rebolledo, Carlos-Alberto; Barragán-Paredes, Maria-Alejandra (Universidad Pedagógica y Tecnológica de Colombia, 2021)
A very important stage in the oral rehabilitation process of patients with dental implants is the provisionalization, which gives an idea of the future restoration and allows the creation of the gum emergency profile, but also allows the patient to have an aesthetic and functional solution until the definitive prostheses are manufactured. To support the provisional restoration, temporary abutments are used; these can be metallic or polymeric. Currently, the most implant-producing companies supply temporary abutments made of polyether ether-ketone (PEEK), an aesthetic material with good mechanical properties but with poor adherence to polymethylmethacrylate (PMMA). Considering that PMMA is the most used material for the manufacture of temporary crowns, but its adhesion with the current abutments is not the best, different investigations have been carried out to improve this union. This work proposes the use of temporary abutments manufactured by 3D printing from a photopolymer resin, which has already had other applications in the dental field. The mechanical properties of the prefabricated PEEK abutments were compared with the abutments obtained by 3D printing, finding that in the comprehension tests, the PEEK abutments performed better with a statistically significant difference; no significant differences were found in the flexion tests; while in the adherence tests resin abutments had a better performance, the difference being statistically significant.